UNDERSTANDING DIVERSITY IN SBM ITB : A COMMUNICATION STYLE APPROACH - Kautsar, Barikh Bill; Pratama, Andika Putra (Journal of Business and Management, 2018)
Abstract. An educational institution consists of a variety of individuals with different backgrounds. The number of backgrounds will affect the environment of an institution. One aspect that shapes an environment is a style of communication. Communication style is a characteristic of communication by an individual to communicate with other individuals. The number of individuals results in communication styles diversity. Communication style which occured in an institution can help to figure what type of people exist in the institution, and what the environment is like. Therefore, a communication style analysis of an institution is quite important to know the environment of an institution. In this study, the author aims to find out the communication style that is most dominant in the SBM ITB environment and how the difference is between one style of communication with each other. SBM ITB is a business school inside the Bandung Institute of Technology (ITB) which is one of the best business school in Indonesia. The author uses survey method by filling out the "P Case" questionnaire total of 129 individuals in participated in this research. There are 93 lecturers and 72 staff as the population of SBM ITB. The sample size of this research defined using the Slovin’s formula. The respondents of this research are lecturers and staff. They are selected by the author because they represent the organizational value of SBM ITB. The results found by the author are that the most dominant communication style is the Idea Style and the least dominant is People Style. The author advises that in dealing with the SBM ITB environment, several adaptations are needed to fit and to balance the communication style within SBM ITB environment.Key words: Communication Style, Communication Diversity, Educational Institution, Business School, SBM ITB